The Assessment of Long-Term Manpower Requirements - Proulx, Pierre-Paul (Relations industrielles / Industrial Relations, 1965)
In his paper, the author presents methods to forecast long-term manpower requirements : employer interviews, extrapolation of trends derived from historical data, standard growth curves, examination of the technology and manpower demand in new firms and industries, study of occupational growth prospects and requirements, comprehensive econometric models. And finally, the article contains a brief examination of French and American current research and practices in long-term manpower forecasting.